2022
DOI: 10.3390/ijerph19137936
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of n-3 Long-Chain Polyunsaturated Fatty Acids to the Prevention of Breast Cancer Risk Factors

Abstract: Nowadays, diet and breast cancer are studied at different levels, particularly in tumor prevention and progression. Thus, the molecular mechanisms leading to better knowledge are deciphered with a higher precision. Among the molecules implicated in a preventive and anti-progressive way, n-3 long chain polyunsaturated fatty acids (n-3 LC-PUFAs) are good candidates. These molecules, like docosahexaenoic (DHA) and eicosapentaenoic (EPA) acids, are generally found in marine material, such as fat fishes or microalg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 126 publications
0
17
0
Order By: Relevance
“…N-3 long-chain polyunsaturated fatty acids (PUFAs), such as DHA, are recognized as potential agents to counteract invasive breast cancer and prevent cancer in animal models [ 50 ]. In rat models with a DHA-rich diet, DHA has been shown to act synergistically with doxorubicin and enhance its effectiveness against drug-resistant cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N-3 long-chain polyunsaturated fatty acids (PUFAs), such as DHA, are recognized as potential agents to counteract invasive breast cancer and prevent cancer in animal models [ 50 ]. In rat models with a DHA-rich diet, DHA has been shown to act synergistically with doxorubicin and enhance its effectiveness against drug-resistant cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Enriching cell membranes with DHA has been found to promote changes in membrane properties and membrane-mediated signaling pathways that elicit anticancer responses [ 48 , 49 ]. The n-3 LCPUFA content of membrane phospholipids is a crucial component of the dynamic and asymmetric cellular membrane that can enhance the cells’ ability to respond to chemotherapy [ 50 ]. Incorporating EPA and DHA into lipid rafts increases the clustering of large raft domains, which can act as mobile docking platforms to improve cell signaling transduction through protein/lipid trafficking, leading to increased cancer cell death [ 37 , 39 , 42 , 49 , 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…DHA plays many physiologic roles including regulation of membrane fluidity, neurotransmitter release, gene expression, myelination, and cell differentiation and growth (Weiser et al., 2016 ). Importantly, it is well known that DHA alone or in combination with chemotherapeutic agents induce cell cycle arrest, apoptosis, autophagy, and tumor growth inhibition by multiple mechanisms such as influencing cell membrane lipid composition, especially that of lipid raft, which leads to a significant modification of their physical–chemical properties altering the content and function of transmembrane proteins including receptors, growth factors, and ATP-binding cassette transporters (Siddiqui et al., 2011 ; Corsetto et al., 2017 ; Giordano et al., 2020 ; Chen et al., 2021 ; Y. Liu et al., 2021 ; Fodil et al., 2022 ; L. Huang et al., 2022 ). Many clinical trials revealed that supplementation with DHA/Eicosapentaenoic acid during cancer treatment could improve a variety of outcomes important to the patient and the disease process, including immune system modulation, improved weight maintenance, and increased disease-free or progression-free survival (Newell et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Important properties of omega-3 PUFAs may explain the reasons underlying their frequent inclusion in nanoformulations designed for cancer therapy, and BCa in particular. Among them, there are their powerful and widely demonstrated anti-inflammatory and anti-cancer activities [ 2 , 29 , 30 , 31 ]. Their anti-inflammatory property has been often invoked to explain their cancer-preventive effects, as well as their efficacy in inhibiting the deleterious side effects frequently associated with chemotherapy [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their anti-inflammatory property has been often invoked to explain their cancer-preventive effects, as well as their efficacy in inhibiting the deleterious side effects frequently associated with chemotherapy [ 32 , 33 ]. However, plenty of preclinical studies have shown that these FAs may exert other and more direct and specific anticancer activities at molecular levels [ 30 , 34 , 35 , 36 , 37 ]. Moreover, it was also shown that they can potentially increase cancer cell sensitivity to conventional antineoplastic therapy [ 38 ].…”
Section: Introductionmentioning
confidence: 99%